2019
DOI: 10.1002/aqc.3042
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometric methods as complementary tools to investigate variability in common dolphins (Delphinus sp.) using museum specimens

Abstract: 1. The common dolphin (Delphinus delphis) has a worldwide distribution, from tropical to temperate seas and oceans. Because of the high degree of geographic variation, the taxonomy of the species is still uncertain.2. Skulls from 195 museum specimens from nine marine areas were examined using two-and three-dimensional geometric morphometrics. Size and shape variations were analysed using univariate and multivariate statistics among and within areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Perrin (1984) noted that they were of an intermediate size between those in the NE Atlantic population, with maximum lengths of 250 cm for males and 252 cm for females reported in recent years (Murphy, Pinn, & Jepson, 2013; Read, 2016), and the Black Sea sub‐species D. delphis ponticus , with maximum lengths of 219 cm for males and 200 cm for females (Amaha, 1994; Perrin, 1984). As in other geographic regions, common dolphins in the Mediterranean Sea exhibit sexual size dimorphism, with males reported as larger than females in cranial size (Nicolosi & Loy, 2021).…”
Section: Strandingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Perrin (1984) noted that they were of an intermediate size between those in the NE Atlantic population, with maximum lengths of 250 cm for males and 252 cm for females reported in recent years (Murphy, Pinn, & Jepson, 2013; Read, 2016), and the Black Sea sub‐species D. delphis ponticus , with maximum lengths of 219 cm for males and 200 cm for females (Amaha, 1994; Perrin, 1984). As in other geographic regions, common dolphins in the Mediterranean Sea exhibit sexual size dimorphism, with males reported as larger than females in cranial size (Nicolosi & Loy, 2021).…”
Section: Strandingsmentioning
confidence: 89%
“…Just as genetic diversity may shed light on population structure, phenotypic diversity may also reveal distinguishing features possibly shaped by directional selection or phenotypic plasticity (Ben Cohen & Dor, 2018). Spatial distinction in skull morphology of D. delphis between southern Sicily and the Tyrrhenian Sea was found after cranial morphometric analyses of museum specimens (Nicolosi & Loy, 2021). The ones from the Tyrrhenian Sea were found to be characterized by a slender skull and a narrower occipital region, suggesting adaptations to different foraging resources and potential ecological separation from the dolphins found in southern Sicilian and North African waters.…”
mentioning
confidence: 99%
“…Today, the only known areas where the Mediterranean common dolphin is relatively abundant are the Alboran Sea (Cañadas & Hammond, 2008) and the waters off Malta (Vella, 1999(Vella, , 2000(Vella, , 2005. Records of the species are also documented in the Pelagos Sanctuary area, in the Sicily Channel near Lampedusa island and in Messina Strait (Pace et al, 2015), off western Sardinia (IUCN, 2012), Israel (Boisseau et al, 2010;Kerem et al, 2012), eastern Ionian Sea (Frantzis, 2009), Aegean Sea (Dede & Öztürk, 2007;Frantzis, 2009;Ryan et al, 2014), and Cap Bon area (northern Tunisia) (Benmessaoud, Chérif, Bradai, & Bejaoui, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This differentiation is likely to have evolved recently and to have been reinforced by a bottleneck event that recently affected the Ionian common dolphins (Moura, Natoli, Rogan, & Hoelzel, 2013). A recent study on skull morphometrics (Nicolosi & Loy, 2019) found that Mediterranean dolphins are highly divergent from oceanic stocks and showed the highest variability in shape. The authors also found a significant distinction between southern and northern samples.…”
Section: Introductionmentioning
confidence: 99%
“…In particular-in analogy to the interpretation of genetic distancesmorphological differences between populations may indicate local adaptation (Colangelo et al, 2012;Meloro, 2011;Meloro, Guidarelli, Colangelo, Ciucci, & Loy, 2017). Current conservation studies of endangered taxa rarely use morphological data to determine phenotypic differentiation below the species level (Dierickx, Shultz, Sato, Hiraoka, & Edwards, 2015;Wilting et al, 2015); and most quantitatively rigorous assessment of phenotypic differentiation remains the domain of taxonomic studies (Celik et al, 2019;Meloro et al, 2017;Nicolosi & Loy, 2019;Senczuk et al, 2018;Sveegaard et al, 2015). Therefore, quantifying morphological variation within a species represents a largely untapped potential for understanding the phenotypic variation between taxonomic units and testing of hypotheses of adaptation and relatedness within a species.…”
Section: Introductionmentioning
confidence: 99%